Does the language you speak at home affect the size of your L2 vocabulary?. Issue 5 (20th October 2018) - Mitits, Lydia; Alexiou, Thomaϊ; Milton, James
ABSTRACT: Language learning strategies are not confined to the classroom but can be extended to cover the whole context of learning. Where learners are part of a minority language group within a much larger national language environment, this context can include the language used for everyday life in the home. It might be thought that enhanced exposure through speaking the L2 in the home would advantage these L2 learners. However, research suggests this may not be the case and in expatriate communities, the promotion of the L1 is a factor that appears to help learners in the development of the L2. The study reported in this paper examines the effect of the language of the home among a group of Muslim minority Turkish language speakers living in Greece and receiving education through the medium of Greek and Turkish. The results of this study suggest that these learners are likely to integrate poorly into their Greek national language environment because of the low level of Greek they attain. However, even here the benefits of promoting the growth and development of the Turkish L1 are apparent since the best developed L1 Turkish vocabularies also grow the largest L2 Greek vocabularies. There are statistically significant gender effects visible in the data where the girls in the study out-perform the boys and, while this appears to be related to the use of Turkish in the home, it is not fully understood.